A political-economy theory of trade agreements - Maggi, Giovanni 1964-; Rodríguez-Clare, Andrés (National Bureau of Economic Research, 2005)
"We develop a model where trade agreements -- in addition to correcting terms-of-trade externalities -- help governments to commit vis-a-vis domestic industrial lobbies. The model allows us to explore how the characteristics of the political environment affect the structure of the trade agreement and the extent of trade liberalization. The model also highlights the role of intersectoral capital mobility in determining trade liberalization. In a dynamic extension of the model, we explore the extent to which trade liberalization occurs gradually, and how its speed depends on the fundamentals of the problem"--National Bureau of Economic Research web site.
Keywords: Politik; Commercial treaties -- Political aspects